'It's up to the market to decide': Revealing and concealing power in the sustainable tea supply chain. (September 2021) - Archer, Matthew; Elliott, Hannah
In 2007, Unilever, the world's largest tea company, announced plans to source its entire tea supply sustainably, beginning with the certification of its tea producers in East Africa to Rainforest Alliance standards. As a major buyer of Kenyan tea, Unilever's decision pushed tea producers across Kenya to subscribe to Rainforest Alliance's sustainable agriculture standard in order to maintain access to the global tea market; according to a 2018 report, over 85% of Kenya's tea producers were Rainforest Alliance certified. Drawing on ethnographic material among supply chain actors across different sites along the sustainable tea value chain (from those designing and disseminating standards to tea traders to smallholder tea farmers), this article examines how these actors frequently attributed the power to determine the outcomes of certification to a faceless 'market'. Deferring to 'the market', we observe, served primarily to mask the outsized power of lead firms (in particular Unilever) to determine conditions of tea production and trade. At the same time, 'the market' was also in some cases qualified by our interlocutors, allowing them implicitly (and at times explicitly) to reveal power and give it a face. Concealing and revealing power in this way, we suggest, can be seen as a mode of engagement among supply chain actors operating in 'sustainable' supply chains, like the Rainforest Alliance-certified Kenyan tea supply chain, in which the power of lead firms tends to be consolidated through market-driven sustainability initiatives. Such a mode of engagement mitigates exclusion from sustainable supply chains while maintaining space for critique.